Teaching undergraduate political methodology - Brown, Mitchell; Nodyke, Shane; Thies, Cameron G.; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2022)
"Providing expert advice from established scholars in the field of political science, this engaging book imparts informative guidance on teaching research methods across the undergraduate curriculum. Written in a concise yet comprehensive style, it illustrates practical and conceptual advice, alongside more detailed chapters focussing on the different aspects of teaching political methodology. Each chapter draws on practised teaching methods covering the what, how and when for teaching political methodology with an in-depth look at systematic research methods. The book is split into four distinct sections for undergraduate research methods education: the approach, the foundations of research design, quantitative analysis and qualitative data. All the advice is evidence-based and grounded in the science of teaching and learning (SoTL) literature from experienced, award-winning and highly recognized instructors of political methodology. Teaching Undergraduate Political Methodology will be required reading for faculty wanting to establish excellent methods for challenging subjects within the fields of political science, public administration and public policies. It will also serve as a useful resource for instructors wishing to gain greater student engagement with their courses by utilising different methods"--
Contents: Introduction to teaching undergraduate political methodology / Mitchell Brown, Shane Nordyke, and Cameron Thies -- Part I: Approaching research methods in the political science curriculum -- 1. What should be taught and when / Charles C. Turner -- 2. The case for an applied approach to teaching research methods / Laura C. Bucci -- 3. Students as consumers and producers: The research methods course and information literacy / B. Gregory Marfleet -- 4. Teaching political methodology to undergraduate students / John Ishiyama -- 5. Teaching political methodology / Mandie Weinandt -- 6. What do we teach with? An examination of texts / Christopher N. Lawrence -- 7. Teaching writing about political science research / Kaye Usry and Joel T. Shelton -- Part II: Foundations of research design -- 8. Questions, queries and problems / Joe Weinberg -- 9. Hypotheses and research expectations / H. Whitt Kilburn -- 10. Teaching experimental and quasi-experimental designs / Federico Vegetti -- 11. The history and art of sampling / Theodore Arapis -- 12. Causality reasoning: What it is and how to teach it / Tom Ellington -- 13. It's actually not in the syllabus: Incorporating ethics in research methods courses / Christi Siver -- Part III: Quantitative analysis for undergraduate research methods education -- 14. How to teach descriptive statistics / Joice Chang -- 15. Bivariate regression: A good beginning makes a good ending / Babak RezaeeDaryakenari -- 16. Basics of multivariate analysis / Emily Clough -- 17. Practical extensions of regression / Soren Jordan -- 18. Teaching big data / Jennifer Bachner -- 19. Student-led survey projects / Ian G. Anson -- 20. Data visualization / Alexis Henshaw -- Part IV: Qualitative data for undergraduate research methods education -- 21. The case study approach / Weining Ai -- 22. Interviewing / Janet Elise Johnson, Candice D. Ortbals, and Lori Poloni-Staudinger -- 23. Content analysis as an effective teaching tool for critical thinking
Includes bibliographical references and index.
Description based on print record.
Keywords: elektronické knihy; electronic books; Political science -- Study and teaching (Higher); Political science -- Research